Desain Desain Kontruksi Hydrolic Ram Pump Systems Dengan Head Input 3 Meter di Daerah Pedesaan Gondosuli - Probolinggo - Muhammad Helmi Kurniawan; Khusnul Khotimah Ayuningtiyas; Ridho Dwi Syahrial (Unit Penelitian, dan Pengabdian Masyarakat (UPPM) Politeknik ATI Makassar, 2023)
Availability of water is a major problem in several regions in Indonesia. There are several areas, especially in Gondosuli Village, Probolinggo, which can only maximize water use during the rainy season. In addition, water has an important role for the people, most of whom work as farmers. Water is one of the main factors affecting the amount of production of agricultural land and fisheries. This problem requires the availability of sustainable water, so that it can meet daily production needs. Therefore it is necessary to use a hydram pump that can work with the help of solar power without using electricity. The working principle of the hydram pump is to convert the kinetic energy of the water flow into dynamic pressure, and as a result a water hammer is created to create high pressure in the air pipe. With the design and construction of the Hydraulic Ram Pump System, it is hoped that it can address the availability of water in a sustainable manner, so that production in agriculture and fisheries can be stable and even increase.